Towards establishing a network of medical libraries a study of the facilitating and hindering factors that influence networking - Encanto, Joenabie A.; Cabbab, Johann Frederick A.; Esposo, Sharon Ma. S.; Santos, Daniel G. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
A library network, as defined by the National Commission on Libraries and Information Science (NCSLIS), is two or more libraries and/or other organizations engaged in a common pattern of information exchange, through communications, for some functional purpose. It usually consists of a formal arrangement whereby materials, information, and services are made available to all potential users.
The need for the establishment of a network of medical libraries in the Philippines has been articulated in recent dialogues among medical librarians and institutions; and both the Medical and Health Librarians Association of the Philippines (MAHLAP) and the Association of Philippines Medical Colleges (APMC) want to explore the feasibility of establishing a network towards resource sharing.
Network establishment has long been discussed within the field of medical librarianship. The reason, however, why it does not materialize has not been explored. For this reason, this study aimed to determine and analyze the factors that facilitate or hinder the establishment of a network of medical libraries as well as to determine whether it would be feasible to establish and sustain the network.
Data were provided by members of MAHLAP and APMC, heads of academic and medical libraries of five institutions, librarians who are members of an existing network and experts with experience in network establishment in the Philippines. There were four research instruments:(1) survey questionnaires, (2) a focus group discussion (FGD) guide, (3) an interview guide for experts and (4) an interview guide for heads of institutions. Frequency analysis and averages were used to interpret the data gathered through survey questionnaires, FGDs and interviews. The data gathered revealed that: (a) most of the respondents were aware of the on-going dialogues regarding the establishment of a network of medical libraries; (b) no demographic characteristics were identified to have influenced level of awareness. The researcher, however, found that the major factor is active participation and/or visibility in MAHLAP's and or APMC's activities; (c) the respondents saw the benefits of having a network of medical libraries but at the same time, acknowledged its disadvantages; (d)only 10 disadvantages were identified, as compared to the 30 network benefits, which showed that most of the respondents saw very few hindering factors and that more are optimistic to join a network; (e) while the MAHLAP Board saw administration support as one factor that may permit them to join a network , they saw it as a factor that may hinder them from joining, i.e. when administrators decline to give support; (f) if the network is established, most of the respondents preferred that they can communicate with other institutions directly than having to go through a coordinators; (g) the respondents gave mixed responses as to who will govern the network of medical libraries; (h) more than 50% of the respondents perceived the network to be established to:facilitate document delivery service, organize and facilitate meetings, fora, symposia, etc., establish referral systems, provide reference service, set up and maintain a union list of serials, provide access to machine-readable database for reference/cataloging purposes, and facilitate interlibrary loan service.(i) given the respondents' opinions, a network policies and guidelines could be drafted for potential network members' discussion and approval; (j) the resources for sharing with the most number of responses are in electronic form as resources in electronic form are easier to transmit or share. There are resources, however, that cannot be shared; (k) most of the respondents did not put much emphasis on budget as a requirement to join a network; and (1) the network's requirements for membership can be met by individual libraries, big or small, only if they could have administrative support.
The researcher recommends that potential member libraries sit down and further discuss the establishment of a network of medical libraries. MAHLAP should take the initiative to convene its members and present to them draft policies and guidelines. Once discussed, this can be submitted to APMC for review and approval by the heads of institutions. Once the invitation for membership is approved, librarians can meet again to finalize the guidelines.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library information networks -- Philippines; Medical libraries -- Philippines